Prognostic significance of tissue and serum HER2 and MUC1 in canine mammary cancer. (July 2015) - Campos, Liliane C.; Silva, Juliana O.; Santos, Fabiana S.; Araújo, Marina R.; Lavalle, Gleidice E.; Ferreira, Enio; Cassali, Geovanni D.
The aim of our study was to compare serum levels and protein tissue of human epidermal growth factor receptor–2 proto-oncogene (HER2) and mucin 1 (MUC1) using an antigen-capture enzyme-linked immunosorbent assay and immunohistochemistry (IHC) in canine mammary carcinomas and investigate how the 2 markers correlate with dogs with metastasis and without metastasis to a regional lymph node. Forty-eight female dogs were selected, including 14 with non-metastatic cancer, 14 with lymph node metastasis, and 20 healthy animals. Serum samples were collected from all the animals and tissues from 28 dogs with malignant mammary tumor with or without metastasis for evaluated HER2 and MUC1 expression. Tissue sample were evaluated for MUC1 and HER2 immunoexpression by IHC. The results showed measurable serum levels of MUC1 and HER2 in all groups. While serum MUC1 levels were significantly higher in animals with metastasis than the other 2 groups, no increase was observed in HER2 serum levels. The MUC1 IHC results showed that only membrane immunostaining was significantly different between the groups. Statistically, there was an association between immunostaining and the serum HER2 levels. Our results indicate that serum concentrations of HER2 and the IHC staining pattern for HER2 in primary tumor do not correlate with the presence of regional metastasis. However, increased concentrations of MUC1 in the serum of dogs with mammary cancer are associated with the presence of metastasis to regional lymph nodes. A membrane pattern of IHC staining for MUC1 in the primary tumor suggests that metastases to regional lymph node are present.